2018
DOI: 10.2147/ott.s172084
|View full text |Cite
|
Sign up to set email alerts
|

miR-517a promotes Warburg effect in HCC by directly targeting FBP1

Abstract: PurposeHepatocellular carcinoma (HCC) is one of the most aggressive malignancies worldwide. Our aim is to explore the expression and biological function of miR-517a in HCC.Materials and methodsWe performed qRT-PCR to detect the expression of miR-517a in clinical samples and cell lines. CKK-8 assay and colony formation assay were employed to detect the miR-517a regulated cell proliferation. Glucose uptake and lactate production were examined to determine the Warburg effect. We also performed ECAR assay using Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…In this study, GSEA analysis showed that high expression of TOP2A was closely associated with cell cycle. Fluorescence activated Cell Sorting (FASC) showed that TOP2A knockdown could inhibit cell proliferation by inducing cell cycle arrest from G2 to M phase, which is consistent with previous reports 20 . In this pathway CDK1-Cyclin B1 complex plays an important role in promoting the G2/M phase transition.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, GSEA analysis showed that high expression of TOP2A was closely associated with cell cycle. Fluorescence activated Cell Sorting (FASC) showed that TOP2A knockdown could inhibit cell proliferation by inducing cell cycle arrest from G2 to M phase, which is consistent with previous reports 20 . In this pathway CDK1-Cyclin B1 complex plays an important role in promoting the G2/M phase transition.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, miRNA is considered as oncogenes or tumor suppressor genes respectively 15 . For example, studies showed that miR-218 and miR-200 prevent the proliferation and metastasis of HCC cells whereas miR-330 and miR-517a promote the development of HCC 17 - 20 . Other studies reported that miR-144-3p functions as a key suppressor of HCC but the underlying mechanism is to be further identified 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic reprogramming, a key feature of which is the Warburg effect, is widely recognized as a major hallmark of cancer, including HCC [71,[85][86][87][88][89][90][91][92][93][94][95]. Several studies not only suggested that tumor cells depend on glycolysis as a primary energy source but also implicated mitochondrial dysfunction in the initiation and progression of HCC [85,[92][93][94].…”
Section: Hcc and Shifted Mitochondrial Metabolismmentioning
confidence: 99%
“…Several miRNAs have been shown to play a potential role in glycolysis and to be associated with HCC progression. These include miR-199a-5p, miR-517a, miR-885-5p, miR-129-5p, and miR-3662 [87][88][89]96]. While miR-517a acts as an oncogene to promote glycolysis in HCC, miR-199a-5p and miR-885-5p suppress glucose consumption, lactate production, cell proliferation, and tumorigenesis in liver cancer cells by targeting HK2 [87,88,96].…”
Section: Hcc and Shifted Mitochondrial Metabolismmentioning
confidence: 99%
See 1 more Smart Citation